Anxiety, Depression and Stress among Undergraduate Students: A Comparative Study of Mathematics and Engineering Students: Examining the Impact of Faculty and Gender on Anxiety, Depression, and Stress Levels among Undergraduate Students (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Anxiety, depression and stress have been pervasive and severe disorders. The utterance of any of these ailments in human life reflects the prevalence of hurdles. These not only obstruct the physical and mental health of young minds but also hamper other prospects in their lives such as academic success, personal contacts, social relations and family bonds. The present study was conducted on a sample of 201 undergraduate students. A standardised tool was employed to collect data which were computed using Pearson product moment correlation coefficient (r) and multivariate analysis of variance (MANOVA). In this throat cutting competitive era, most learners get suffered from anxiety, depression and stress which cause unrest, dropouts and even suicide attempts. An apparent height of such cases in academic institutions has led the researchers to explore these constructs. Thus, the present research is an earnest attempt to find out the difference in anxiety, depression and stress of undergraduate students in terms of faculty and gender. It also examined the association between anxiety, depression and stress. The results uncovered that there was a significant relationship between anxiety, depression and stress of undergraduate students. There was a significant multivariate main effect of faculty on the combined dependent variables anxiety, depression and stress. There was a significant univariate main effect of faculty on anxiety. Science students had a higher anxiety level than engineering students. There was a significant univariate main effect of faculty on depression. Engineering students had a higher depression level than science students. There was a non-significant univariate main effect of faculty on stress, but engineering students had a bit higher level of stress than science students. There was a significant multivariate main effect of gender on the combined dependent variables anxiety, depression and stress. There was a significant univariate main effect of gender on anxiety and depression. Females had higher scores on anxiety and depression than males. There was a non-significant univariate main effect of gender on stress, but female students scored a bit higher on stress than male students. There was a non-significant multivariate interaction effect of faculty and gender on the combined dependent variables anxiety, depression and stress.